STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KETERAMPILAN PRODUKTIF DI PKBM RAWASARI, JAKARTA TIMUR - Puji Hadiyanti (Perspektif Ilmu Pendidikan, 2008)
Community participation is very important to achieve the objectives of any training or learning process. This qualitative research was conducted in the Center for Teavhing and Learning Activities (PKBM) in Rawasari, Jakarta, aiming at discovering the strategy applied in the Center. Based on the data collected and analysed, this research finds out notable progress achieved, but the the Center has not implemented wholistic strategy. Beside identifying some problems, this research provides a set of recommendation related to improving the exisiting strategy to empower the communitythrough productive competence.